RETRACTED: Targeting posttranslational modifications of RIOK1 inhibits the progression of colorectal and gastric cancers - Xuehui Hong; He Huang; Xingfeng Qiu; Zhijie Ding; Xing Feng; Yuekun Zhu; Huiqin Zhuo; Jingjing Hou; Jiabao Zhao; Wangyu Cai; Ruihua Sha; Xinya Hong; et al. (eLife)
RIOK1 has recently been shown to play important roles in cancers, but its posttranslational regulation is largely unknown. Here we report that RIOK1 is methylated at K411 by SETD7 methyltransferase and that lysine-specific demethylase 1 (LSD1) reverses its methylation. The mutated RIOK1 (K411R) that cannot be methylated exhibits a longer half-life than does the methylated RIOK1. FBXO6 specifically interacts with K411-methylated RIOK1 through its FBA domain to induce RIOK1 ubiquitination. Casein kinase 2 (CK2) phosphorylates RIOK1 at T410, which stabilizes RIOK1 by antagonizing K411 methylation and impeding the recruitment of FBXO6 to RIOK1. Functional experiments demonstrate the RIOK1 methylation reduces the tumor growth and metastasis in mice model. Importantly, the protein levels of CK2 and LSD1 show an inverse correlation with FBXO6 and SETD7 expression in human colorectal cancer tissues. Together, this study highlights the importance of a RIOK1 methylation-phosphorylation switch in determining colorectal and gastric cancer development.